Iron homeostasis in the Rhodobacter genus - Zappa, Sébastien (2013)
Metals are utilized for a variety of critical cellular functions and are essential for survival. However cells are faced with the conundrum of needing metals coupled with e fact that some metals, iron in particular are toxic if present in excess. Maintaining metal homeostasis is therefore of critical importance to cells. In this review we have systematically analyzed sequenced genomes of three members of the Rhodobacter genus, R. capsulatus SB1003, R. sphaeroides 2.4.1 and R. ferroxidans SW2 to determine how these species undertake iron homeostasis. We focused our analysis on elemental ferrous and ferric iron uptake genes as well as genes involved in the utilization of iron from heme. We also discuss how Rhodobacter species manage iron toxicity through export and sequestration of iron. Finally we discuss the various putative strategies set up by these Rhodobacter species to regulate iron homeostasis and the potential novel means of regulation. Overall, this genomic analysis highlights surprisingly diverse features involved in iron homeostasis in the Rhodobacter genus.